Neurobiological responses in the adolescent striatum to being 'tested'. Issue 1 (6th December 2018) - DePasque, Samantha; Galván, Adriana
Abstract: While emerging research implicates the striatum in adolescents' ability to learn from feedback, little is known about how motivational contexts, such as emphasizing the evaluative nature of learning tasks, modulate adolescents' striatal learning. We used functional magnetic resonance imaging during a feedback-based learning task, in conjunction with a within-subject evaluative threat manipulation, to determine whether evaluation threat influences behavioral and neural responses to feedback in adolescents. On average, adolescents were less sensitive than adults to the evaluation threat. In the adolescents, the effect of evaluation threat on performance was tracked with the striatal response to performance feedback during the evaluation threat condition, such that greater striatal sensitivity correlated with greater gains in learning performance. Our findings suggest that variability in how adolescents respond to a contextual threat of evaluation and associated striatal sensitivity can facilitate enhanced learning.